AÇAÍ IN THE GLOBALIZATION MODEL OF AMAZON PLANTS: AN ANCIENT PRODUCT, NEW FORMS OF SPATIAL PRODUCTION AND REPRODUCTION - Cortezzi, Francisco (Geosaberes; Vol 11 (2020): Vol 11 (2020)DO - 10.26895/geosaberes.v11i0.975, 2020)
Originating from the palm Euterpe oleracea, the açaí is an endemic fruit of the Amazon rainforest, the consumption of which has grown strongly in Brazil since the 1990s and is emerging in other regions of the world. Consumed mainly in the form of pulp and erected as a "superfruit" by marketing players for its antioxidant and nutritional potential, the açaí berry goes through a dynamic process encompassing both its space production and international distribution circuit as well as its composition derivative products. In this conjuncture, our main objective is to understand the metamorphosis of the acai, that is to say when it is perceived much more as an economic resource than as a natural resource. To achieve this objective, our research uses as a main basis the Globalization Model of Amazonian Plants, proposed and developed by Beaufort (2017).